The Roots of Japanese Legal Terminology - Horie, Yuki (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
During the Meiji era, Japan began its modernization and the Western culture was introduced to Japan. Japan had to construct a modern society, fusing complicatedly with a model of the Japanese tradition. In the legislation field, beginning with the Constitution of the Empire of Japan, the establishment of the first unified nationwide law was attempted in this period. In particular concerning the civil code, The French Code (later German Code) was considered as the most comprehensive code, and its translation was made and edited as a Japanese Civil Code. However, translating the original concepts which had not existed in Japan was a very difficult task. They coined words preserving the original sequence of elements and as a result there is a gap between the European legal terms and the Japanese ones especially in translation. The current legal terminology was made based on such a historical background, in consequence it has become less familiar to Japanese people. I would like to consider theses problems on some examples.

明治時代の文明開化に伴い、西欧の文化が日本に流入した。日本は独自の制度や文化を維持しつつ、西欧文化を取り入れながら近代化をすすめていった。法律においても、憲法制定を始めとし、日本で始めて国内を統一する法律の制定が行われた。民法においては特にフランス、のちにドイツの民法が手本とされ、これらの民法の日本語への翻訳作業が行われた。しかしながら、もともと日本に存在しなかった概念を翻訳することは、非常に困難な作業であり、結果的に誤訳や意味不明瞭な造語が多く生まれた。現在の法律用語はその ような歴史的背景をもとに成り立っているため、なお多くの一般の日本人にとって意味不明で親しみにくい言語となっている。これらの法律用語が造語された過程についていくつか例をあげて考察したいと思う。
Źródła japońskiej terminologii prawnej i prawniczej
日本語における翻訳語としての法律用語の歴史